The effects of international trade on gender inequality: women carpet weavers of Iran - Zahra Karimi (Levy Economics Institute of Bard College, 2008)
The process of economic globalization has winners and losers. Iran's carpet industry provides a good illustration of the adverse side of this process. As the production costs of its rivals have fallen, surging international trade has reduced the market share of Iran's labor-intensive products, especially Persian carpets. This paper reports the findings of an informal survey of carpet weavers conducted in and around the Iranian city of Kashan, showing how harsh international competition has reduced the weavers' real wages and restructured the labor force of the industry and poor Afghan immigrant householders and their children are increasingly taking the place of Iranian weavers. Furthermore, weaving is consistent with the subordinate position of women carpet weavers within the household; as a form of employment, it has hardly affected the social status quo.
Keywords: F14; F16; J16; J31; J41; 330; International trade; gender inequality; Iran; race to the bottom; hand woven carpet